Three pairs of fungal Trametes strains isolated from distinct geographic origins show conserved genomic features and adaptive response to plant biomass - E. Drula; D. Navarro; J. Lambert; D. Chaduli; A. Lomascolo; C. Heilmann; S. Grisel; K. Barry; K. Labutti; B. Andreopoulos; L. Siyoun; S. Tejomurthula; et al. (Bioresource Technology, 2026)

Gene family expansions and transcriptome signatures uncover fungal adaptations to wood decay - Hayat Hage; Shingo Miyauchi; Máté Virágh; Elodie Drula; Byoungnam Min; Delphine Chaduli; David Navarro; Anne Favel; Manon Norest; Laurence Lesage‐Meessen; Balázs Bálint; Zsolt Merényi; et al. (Environmental Microbiology, 2021)
Summary Because they comprise some of the most efficient wood‐decayers, Polyporales fungi impact carbon cycling in forest environment. Despite continuous discoveries on the enzymatic machinery involved in wood decomposition, the vision on their evolutionary adaptation to wood decay and genome diversity remains incomplete. We combined the genome sequence information from 50 Polyporales species, including 26 newly sequenced genomes and sought for genomic and functional adaptations to wood decay through the analysis of genome composition and transcriptome responses to different carbon sources. The genomes of Polyporales from different phylogenetic clades showed poor conservation in macrosynteny, indicative of genome rearrangements. We observed different gene family expansion/contraction histories for plant cell wall degrading enzymes in core polyporoids and phlebioids and captured expansions for genes involved in signalling and regulation in the lineages of white rotters. Furthermore, we identified conserved cupredoxins, thaumatin‐like proteins and lytic polysaccharide monooxygenases with a yet uncharacterized appended module as new candidate players in wood decomposition. Given the current need for enzymatic toolkits dedicated to the transformation of renewable carbon sources, the observed genomic diversity among Polyporales strengthens the relevance of mining Polyporales biodiversity to understand the molecular mechanisms of wood decay.

Comparative genomics of Mortierella elongata and its bacterial endosymbiont Mycoavidus cysteinexigens - J. Uehling; A. Gryganskyi; K. Hameed; T. Tschaplinski; P. K. Misztal; S. Wu; A. Desirò; N. Vande Pol; Z. Du; A. Zienkiewicz; K. Zienkiewicz; E. Morin; et al. (Environmental Microbiology, 2017)
Summary Endosymbiosis of bacteria by eukaryotes is a defining feature of cellular evolution. In addition to well‐known bacterial origins for mitochondria and chloroplasts, multiple origins of bacterial endosymbiosis are known within the cells of diverse animals, plants and fungi. Early‐diverging lineages of terrestrial fungi harbor endosymbiotic bacteria belonging to the Burkholderiaceae. We sequenced the metagenome of the soil‐inhabiting fungus Mortierella elongata and assembled the complete circular chromosome of its endosymbiont, Mycoavidus cysteinexigens , which we place within a lineage of endofungal symbionts that are sister clade to Burkholderia . The genome of M. elongata strain AG77 features a core set of primary metabolic pathways for degradation of simple carbohydrates and lipid biosynthesis, while the M. cysteinexigens (AG77) genome is reduced in size and function. Experiments using antibiotics to cure the endobacterium from the host demonstrate that the fungal host metabolism is highly modulated by presence/absence of M. cysteinexigens . Independent comparative phylogenomic analyses of fungal and bacterial genomes are consistent with an ancient origin for M. elongata – M. cysteinexigens symbiosis, most likely over 350 million years ago and concomitant with the terrestrialization of Earth and diversification of land fungi and plants.